Reading nonfiction text on an iPad in a secondary classroom. (20th January 2017) - Cardullo, Victoria; Zygouris‐Coe, Vassiliki "Vicky" I.; Wilson, Nance S.
Abstract : The intent of this research was to investigate the experiences of eighth grade readers as they read nonfiction text on an iPad for academic purposes. We investigated reading strategies that students use to support their reading as well as what role iPad features played in the reading process. New literacies, metacognition and transactional theories informed the framework. Multiple data sources were used to triangulate findings and included (a) retrospective think alouds, (b) student iPad survey, (c) pre and post study student interviews, (d) Metacognitive Awareness of Reading Strategies Inventory and (e) student observations. Data for the collective case study participants focused on the identification of proficient readers who displayed confidence, competency, and control over text. Themes identified in the collective case studies included (a) reading comprehension strategies, (b) nonfiction features and (c) iPad features to support their reading of nonfiction on the iPad.